Evidence of Chikungunya Virus Disease in Pakistan Since 2015 With Patients Demonstrating Involvement of the Central Nervous System - Barr, Kelli L.; Khan, Erum; Farooqi, Joveria Q.; Imtiaz, Kehkashan; Prakoso, Dhani; Malik, Faisal; Lednicky, John A.; Long, Maureen T. (Frontiers in Public Health, 2018)
Several arboviruses are endemic to and co-circulate in Pakistan. In recent years, Pakistan has observed a rise in arboviral infections. A cross-sectional study for arboviral diseases, which included screening for Chikungunya virus (CHIKV), was initiated in 2015 to determine which pathogens were causing disease in patients presenting to health care services. Exposure to CHIKV was verified via detection of viral nucleic acids or virus-specific IgM with virus-specific neutralizing antibodies. Out of 997 enrolled patients presenting with clinical features suggestive of arboviral disease, 102 patients were positive for CHIKV IgM antibodies and 60 patients were positive for CHIKV nucleic acids or neutralizing antibodies. The data presented here show that CHIKV has been circulating in Pakistan since April of 2015. CHIKV infections were detected in study subjects up to the conclusion of our enrollment period in July 2017. Syndromic and clinical data show that arthralgia was associated with CHIKV as was rash, fever greater than 38°C, and lymphopenia. Neurological symptoms were reported in 49% of CHIKV suspect patients and in 46.6% of confirmed infections. Acute disseminated encephalomyelitis was diagnosed in 5% of confirmed infection and various manifestation of encephalitis diagnosed in an additional 16.6% of patients with confirmed CHIKV infections. CHIKV-exposed patients were just as likely to present with neurological symptoms and encephalitis as patients with West Nile Virus infections but were 4.57 times more likely to have lymphopenia. This proportion of neurological symptoms may be a complicating factor in countries where WNV and/or JEV co-circulate with CHIKV.